2006
DOI: 10.1007/s00383-006-1704-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of hyperglycemia in FAT/CD36 expression and function

Abstract: FAT/CD36 is a long-chain fatty acid transporter and scavenger receptor for oxidized LDL. Defects in FAT/CD36 have been linked to the hypertriglyceridemia and insulin resistance. Expression of FAT/CD36 was reported increase in type 1 diabetes; however, it remains unclear whether serum glucose or insulin plays an important role in this regulation. To elucidate the individual contribution of plasma glucose and insulin in the regulation of FAT/CD36 mRNA expression, we induced type 1 diabetes in male Sprague-Dawley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Several studies have demonstrated that hyperglycemia-induced CD36 expression mediates cellular dysfunction in various tissues [28], [29]]. This upregulation was found to coincide with increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that hyperglycemia-induced CD36 expression mediates cellular dysfunction in various tissues [28], [29]]. This upregulation was found to coincide with increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinediones, a major new class of drugs to treat diabetes, up regulate CD36 in monocytes/macrophages, adipose and muscle (Wilmsen, Ciaraldi, Carter, Reehman, Mudaliar, & Henry, 2003, Kolak, et al, 2006, Hirakata, Tozawa, Imura, & Sugiyama, 2004,Llaverias, et al, 2006, and may therefore contribute to the insulin-sensitizing effects of these drugs as a result of plasma fatty acid clearance, but also potentially to atherosclerosis and obesity in these patients. Interestingly, glucose/insulin appears to increase CD36 expression (Sampson, Davies, Braschi, Ivory, & Hughes, 2003,Griffin, et al, 2001,Chabowski, et al, 2004,Chen, Yang, Loux, Georgeson, & Harmon, 2006, and because CD36 is expressed on tissues important in fatty acid metabolism (heart, skeletal muscle, fat, and in pathological states, liver) this may imply an important role for CD36 in insulin resistance (see later). Regulation of CD36 expression can be mediated both pre-and post-transcription.…”
Section: Cd36 Regulationmentioning
confidence: 97%
“…Conversely, in human adipose tissue, both isomers induced decreased expression of this gene. It is noteworthy that plasma glucose levels play an important role in the regulation of CD36 expression in adipose tissue (Chen et al, 2006). CA3 (carbonic anhydrase 3) is a key enzyme in fatty acid synthesis that is downregulated by t10,c12 CLA in adipose tissue (Herrmann et al, 2009).…”
Section: Molecular Targets Of Conjugated Linoleic Acidmentioning
confidence: 99%